Female chief financial officers (CFOs) and environmental decoupling. The moderating impact of sustainability board committees - Velte, Patrick (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This study analyses the link between chief financial officer (CFO) gender and environmental decoupling. Moreover, the moderator effect of sustainability board committees is tested. Based on upper echelons theory, a sample of listed firms headquartered in the European Union (2312 firm-year observations) from the business years 2017–22 is used. In line with the theoretical framework and based on correlation and regression analyses, CFO gender is significantly and negatively linked with environmental decoupling. The existence of sustainability board committees strengthens this relationship. The results are robust to various robustness tests and endogeneity checks. This study contributes to the increasing research activity on the influence of corporate governance on environmental decoupling. Future research should analyze specific environmental decoupling dimensions and the impact of other CFO characteristics (e.g., expertise) on environmental decoupling. Regarding the stakeholder concerns on corporate environmental decoupling in recent years, firms should increase the quality of their environmental reports to build up increased stakeholder relations. To the best of our knowledge, this is the first empirical study on the relationship between CFO gender and corporate environmental decoupling. Moreover, the moderator effect of sustainability board committees is included as an innovative complementary driver.
Keywords: CFO Gender; Corporate Governance; Corporate Social Responsibility (CSR); Environmental Decoupling; Sustainability Board Committee; Upper Echelons Theory